Managing cultural heritage an international research perspective - Zan, Luca; Baraldi, Sara Bonini; Lusiani, Maria; Shoup, Daniel; Ferri, Paolo; Onofri, Federica (Ashgate, 2015)
Heritage as a field of research and collective action has emerged only in the last 40 years, spurred by the 1972 Unesco World Heritage Convention. Conservation was the touchstone discipline of the field, but the highly interdisciplinary nature of heritage has brought in a wide diversity of perspectives that has sometimes posed challenges to mutual understanding. Since the 1990s, heritage studies has emerged as a distinct academic field, and practices and rhetoric drawn from mainstream corporate management and strategic planning have become widespread. Based on fifteen years of field work done by a group of scholars at the Department of Management, University of Bologna, this book is an in-depth investigation of management practices rather than policies, based on a variety of case studies from around the world. The authors take the issue of management in heritage seriously but also take into account the role of other disciplines within heritage organizations. In particular, they focus on sustainability in terms of financial resources, human resources, knowledge management, and the relationship with the audience and communities of scholars.